A rice cab gene promoter contains separate cis-acting elements that regulate expression in dicot and monocot plants. - Luan, S (1992)
The major light-harvesting chlorophyll a/b binding proteins of the photosynthetic apparatus are encoded by families of nuclear cab genes. The expression of most cab genes is tissue specific and photoregulated in angiosperms. In transgenic tobacco plants, expression of the reporter gene beta-glucuronidase (GUS) is photoregulated and tissue specific from 5' upstream sequences of the rice cab1R gene; deletion of sequences upstream from position -170 with respect to the transcription start site eliminates the enhanced and photoregulated expression in the transgenic plants. Using an in situ transient expression assay, we have determined that the sequence OCT-R, an octamer repeat that lies within the -269 to -170 region of cab1R, is essential for photoregulated expression of the chimeric GUS gene in leaf cells of maize and rice but is not required for expression in illuminated tobacco leaves. Conversely, box III*- and G-box-like sequences found near OCT-R in cab1R are necessary for high-level transient expression of the reporter gene in tobacco leaf tissue but are not required for transient expression in maize or rice leaves.